Szövetségbe ágyazott univerzális normák : Adalékok a Collatio Legum Mosaicarum et Romanarum értelmezéséhez - Herger, Eszter Cs. (Díké - A Márkus Dezső Összehasonlító Jogtörténeti Kutatócsoport folyóirata, 2025)
In 860, the jurist-theologian Hincmar referred to a late antique compilation – cited by him in the context of a marital dispute between King Lothair and his wife Theutberga, within one of the “successor states” of the divided Frankish Empire – as the primi libri legis Romanae (“first book of Roman law”). He also indicated to both his contemporaries and modern readers what principles ‘just judges’ ought to consider, citing two sources: the 9th-century Archbishop of Reims found justice in the Old Testament Scriptures, particularly in the Law of Moses, and in the Roman legal concepts current at the time of the compilation known in European legal history as the Collatio Legum Mosaicarum et Romanarum. In the terminology employed by Hincmar, we hypothesise that – despite the significant chronological gap between the Mosaic legislation and the Roman legal sources integrated into the Collatio – a unifying element can be identified: the conception of justice grounded in universal natural law. This assumption is explored below through an analysis of the Collatio’s provisions on family relations, with particular emphasis on the universal prohibition of incest within the framework of the Noahide covenant.